2003
DOI: 10.1046/j.1440-1843.2003.00507.x
|View full text |Cite
|
Sign up to set email alerts
|

Smokeless tobacco and health in India and South Asia

Abstract: South Asia is a major producer and net exporter of tobacco. Over one-third of tobacco consumed regionally is smokeless. Traditional forms like betel quid, tobacco with lime and tobacco tooth powder are commonly used and the use of new products is increasing, not only among men but also among children, teenagers, women of reproductive age, medical and dental students and in the South Asian diaspora. Smokeless tobacco users studied prospectively in India had ageadjusted relative risks for premature mortality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
353
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 380 publications
(375 citation statements)
references
References 43 publications
20
353
1
1
Order By: Relevance
“…Another study in 1995 in 1110 residents of 2 states, 5-74 years, found that 72% males and 80% females chewed areca nut, 80% of whom incorporated tobacco in their quid. 18 In a house to house survey of 22,000 villagers, aged 15 and above in Bhavnagar district, Gujarat, 7 India 20.4% of males used mawa or betel quid. The popularity of areca nut mixtures, like mawa, pan masala, gutkha spawned an epidemic of SMF.…”
Section: Discussionmentioning
confidence: 99%
“…Another study in 1995 in 1110 residents of 2 states, 5-74 years, found that 72% males and 80% females chewed areca nut, 80% of whom incorporated tobacco in their quid. 18 In a house to house survey of 22,000 villagers, aged 15 and above in Bhavnagar district, Gujarat, 7 India 20.4% of males used mawa or betel quid. The popularity of areca nut mixtures, like mawa, pan masala, gutkha spawned an epidemic of SMF.…”
Section: Discussionmentioning
confidence: 99%
“…The use of these products is strongly associated with oral cancer. [2][3][4] The levels of tobacco-specific nitrosamines in gutka were lower than those in many of the other products examined here, but were still considerably higher than nitrosamine levels in food and other common products, which are typically in the low ppb range. 11,24 Supari, which is similar to gutka but does not contain tobacco, did not have detectable levels of tobacco-specific nitrosamines.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional forms of smokeless tobacco include betel quid containing tobacco, tobacco with lime and tobacco tooth powder but there are also new products with increasing popularity. 2 Chewing of betel quid containing tobacco is a well-established cause of oral cancer in India. [2][3][4] Oral leukoplakia and submucous fibrosis, likely precursor lesions to oral cancer, are also strongly linked to smokeless tobacco use.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…World Health Organization (2008) predicted that tobacco will lead to over 8 million deaths annually by 2030 with low and middle-income countries accounting for 70% of deaths. Smokeless tobacco use in South Asia is believed to be a significant contributor to morbidity and mortality (Gupta and Ray, 2003).…”
Section: Introductionmentioning
confidence: 99%